A study on 3D printing usage among Malaysian users - Idris, Mat Sahat; Ma, Quanjin; M. R. M., Rejab (Faculty Mechanical Engineering, UMP, 2023)
In this research, the use of three-dimensional (3D) printing among Malaysian users was studied. The aim of the research is to establish the demographics and use of 3D printing in Malaysia. A questionnaire was distributed among 3D printing users during a 3D printing webinar and via social media groups consisting of 3D printer users. For the demographic section, 74 males and 8 females responded to the questionnaire, with more than 90% of the respondents have tertiary education. 39% of the respondents are from Greater Klang Valley, and 33% of the respondents are self-employed. The highest application of 3D printing is for hobby (i.e., 67% of the respondents), while the highest response for experience in 3D printing is 28% with 1–3 years of experience. Creality 3D printer brand is the most selected printer brand, with 64.7% of the respondents using the brand. 33% of the respondents used the printer at a heavy usage rate of 5 days per week, which is the highest response. For the material used, 85.4% of the respondents agreed that they normally used polylactic acid, while 79.3% of the respondents selected Cura as the most used software. Furthermore, 79.3% of the respondents stated that the infill percentage setting as the most changed setting, while 63.4% of the respondents agreed that bed levelling is the most common problem in 3D printing. In the opinion section, most of the respondents believed that 3D printing technology is still new and should be taught in schools. Based on the results, the research has successfully established the demographics and usage among 3D printer users in Malaysia.